«SCHOOL OF COMPETENCIES» AS A TECHNOLOGY FOR THE DEVELOPMENT OF STUDENTS’ ADDITIONAL COMPETENCIES AT CLASSICAL UNIVERSITY - V. Y. Stromov; Р. V. Sysoyev; V. V. Zavyalov (Высшее образование в России)
Nowadays many students feel the need to develop a number of additional competencies that will enable them to significantly expand their employment and professional opportunities after graduation. The student government’s research and educational project “School of Competencies” is a modern and growing format in Russian universities for the development of students’ additional professional and general cultural competencies, which include competencies in the legal framework for the organization of their own business, business planning, marketing, advertising and communication with the public, stress resistance, registration of applications for grants, techniques for writing scientific texts, etc. In this paper the authors: a) conduct a brief review of literature and justify the relevance of the “School of Competencies” project for students; b) present the subject content of the “School of Competencies” project and the nomenclature of the professional and general cultural competencies of students; c) develop their own stages of implementation of the “School of Competencies” project in universities.